Reform ripples: The role of recontextualization in scaling up - Tali Aderet-German; Adam Lefstein (Arizona State University, 2021)
This paper explores how educational interventions impact the districts they are implemented in above and beyond their intended outcomes. We argue that such unplanned "ripple effects", in which program elements are recontextualized into other settings, are an important aspect of bringing educational interventions to scale. We analyze these phenomena in one Israeli district in which a teacher leadership and professional learning community initiative has been implemented and rapidly scaled up over the past five years. Extensive longitudinal ethnographic data were collected, including participant-observation in schools, professional development workshops, district management meetings and initiative-related events; 75 interviews with teachers and school and district management; and multiple informal conversations. We identify "ripples" in four arenas, and discuss the importance of individuals as mechanisms for transferring ideas across contexts, the role of ripples in advancing the initiative's ethos, and the ripples' long-term sustainability. Our findings suggest more attention should be paid to the impact of educational reforms on meaningful change beyond their original aims and settings. Alongside possible affordances these ripple effects have in the scaling up process, careful consideration should be given to their latent disadvantages, such as obscuring the program's primary agenda.